The Influence of School Leadership and Management Practices on Sustaining Arts Education Programs in Primary and Secondary Schools - Sanjaya, Iksan; Awalia, Rabiatul; Wahyudi, Wahyudi (Educia Journal, 2023)
The qualitative research question of this study is to analyse the management of schools in supporting arts education, including the administrative practices, resource dimensions, and leadership factors that may enhance the implement of arts education. The study was therefore intended to improve the understanding of how and to what extent school management impacts on the implementation of arts in learning and school climate. Various forms of data were collected: interviews with 31 school principals and arts teachers, administrative staff, focus group interviews with 115 students and 12 parents, and document analysis of school policies, schedules and documents that concern arts education. The study shows that schools, which have clear and strong arts education polices, are in a better place to sustain quality arts instruction. Further, the schools which have separate funds and budgets for the arts and those in which the principals and head teachers positively perceive the worth and importance of the arts usually have more effective and viable learning programs. This research fills the existing literature voids by focusing on the central issue of leadership for appreciable arts climate in schools as well as harmonisation of academic and arts pursuits. The study offers insights to educators and policymakers involved in the provision and development of arts education hence providing tangible suggestions on policy advancements as well as resource and leadership matters. Thus, the present research expands the discussion of how schools may include arts education successfully to become a part of curriculum as one of the foundational elements of learning experiences.